Is It Effective or Not? Countenance Stake Evaluation of the Numeration Learning combination Model for Student in South Papua. - Nirtha, Eva; Tembang, Yonarlianto; Au Hurit, Andreas (Jurnal Mebis, 2024)
This study evaluates the effectiveness of the Numeration Learning Combination Model (NLCM) for students in South Papua by employing the Countenance Stake Evaluation model. The region's educational landscape, characterized by linguistic diversity and resource constraints, necessitates innovative teaching approaches. The NLCM combines traditional pedagogical methods with modern educational technologies and culturally relevant content. This evaluation framework examines antecedents, transactions, and outcomes to provide a comprehensive assessment. Data collection by conducting pre-post tests, observations and interviews. Data analysis techniques use a quantitative and a qualitative approach. Data analysis involves quantitative measures of measure the effectiveness of the learning model using the T test based on student performance with the significance value (Sig. 2-tailed) was obtained of 0.00, less than 0.05 and qualitative insights from educators and students. Initial findings reveal that the NLCM enhances numeracy skills, increases student engagement, supports a more inclusive learning environment and addressing the diverse needs of South Papua's student population. The findings suggest that the NLCM is a viable and effective approach to numeration learning in South Papua context, with potential implications for broader educational strategies in similar regions.